Adaptive Identification of Induction Drive - Janickas, R.; Savickiene, Z. (Elektronika ir Elektrotechnika, 2012)
Because not well known exact parameters of induction motor, on this production used different materials and their nonlinearity the simulation and experimental results differs. Experimental measurements of induction drive are performed. Drive parameters measurements methods are observed. Adaptive identification model including algorithm, comparison of simulated and experimental results is created and presented. DOI: http://dx.doi.org/10.5755/j01.eee.18.8.2604